PENERAPAN REGRESI LOGISTIK ORDINAL UNTUK MENGANALISIS TINGKAT KEPARAHAN KORBAN KECELAKAAN LALU LINTAS KABUPATEN BULELENG - PURNAMI, DEWA AYU MADE DWI YANTI; SUKARSA, I KOMANG GDE; GANDHIADI, G. K. (E-Jurnal Matematika, 2015)
Ordinal logistic regression is a statistical method for analyzing the respone variables that have an ordinal scale consisting of three or more categories. This method is an extension of logistic regression with a binary respone variable. In this study the cases studies was the severity of traffic accident victims in Buleleng. The severity of the victims were divided into three categories: minor injuries, serious injuries and died. This research also used six predictor variables, namely age, hours of accident, education, gender, the status of location, and the venicles involved. Result of study shows that the variables age, hours of accident, education and the status of location have a significan effect on the severity of traffic accident victims.
Keywords: Ordinal logistic regression; severity of traffic accident victims